Thermomechanical damage in cortical bone caused by margins of surgical drill bit: A finite element analysis. (April 2023) - Akhbar, Mohd Faizal Ali
Highlights: Surgical drill margin significantly affects bone's thermomechanical damage. Margin height increases thermal damage but reduces mechanical damage. A higher margin width reduces temperature, thrust force, and torque. Proposed ranges of margin height and width help identify optimal margin design. Improvising the surgical drill bit is possible with a new drill margin design. Abstract: Background and Objective: Conventional surgical drill bits suffer from several drawbacks, including extreme heat generation, breakage, jam, and undesired breakthrough. Understanding the impacts of drill margin on bone damage can provide insights that lay the foundation for improvement in the existing surgical drill bit. However, research on drill margins in bone drilling is lacking. This work assesses the influences of margin height and width on thermomechanical damage in bone drilling. Methods: Thermomechanical damage—maximum bone temperature, osteonecrosis diameter, osteonecrosis depth, maximum thrust force, and torque—were calculated using the finite element method under various margin heights (0.05-0.25 mm) and widths (0.02-0.26 mm). The simulation results were validated with experimental tests and previous research data. Results: : The effect of margin height in increasing the maximum bone temperature, osteonecrosis diameter, and depth were at least 19.1%, 41.9%, and 59.6%, respectively. The thrust force and torque are highly sensitive to margin height. A higher margin height (0.21-0.25 mm) reduced the thrust force by 54.0% but increased drilling torque by 142.2%. The bone temperature, osteonecrosis diameter, and depth were 16.5%, 56.5%, and 81.4% lower, respectively, with increasing margin width. The minimum thrust force (11.1 N) and torque (41.9 Nmm) were produced with the highest margin width (0.26 mm). The margin height of 0.05-0.13 mm and a margin width of 0.22-0.26 produced the highest sum of weightage. Conclusions: A surgical drill bit with a margin height of 0.05-0.13 mm and a margin width of 0.22-0.26 mm can produce minimum thermomechanical damage in cortical bone drilling. The insights regarding the suitable ranges for margin height and width from this study could be adopted in future research devoted to optimizing the margin of the existing surgical drill bit. graphical abstract: Image, graphical abstract